2000
DOI: 10.2307/2640985
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO 2 and the Composition and Function of Soil Microbial Communities

Abstract: Abstract. Elevated atmospheric CO 2 has the potential to increase the production and alter the chemistry of organic substrates entering soil from plant production, the magnitude of which is constrained by soil-N availability. Because microbial growth in soil is limited by substrate inputs from plant production, we reasoned that changes in the amount and chemistry of these organic substrates could affect the composition of soil microbial communities and the cycling of N in soil. We studied microbial community c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
95
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 27 publications
12
95
1
2
Order By: Relevance
“…In a recent experiment, we observed that elevated atmospheric CO # substantially increased net fine-root production only when soil N was in abundant supply . Although the input of organic substrates from fine-root production clearly increased under elevated CO # , we observed no change in the biomass of soil microorganisms during a 3-yr experiment with Populus tremuloides (Zak et al, 2000a). In this soil, fine root biomass was 1\100 of the labile pool of organic matter and 1\1000 of the total organic matter content.…”
Section: Soil Microbial Biomassmentioning
confidence: 77%
See 4 more Smart Citations
“…In a recent experiment, we observed that elevated atmospheric CO # substantially increased net fine-root production only when soil N was in abundant supply . Although the input of organic substrates from fine-root production clearly increased under elevated CO # , we observed no change in the biomass of soil microorganisms during a 3-yr experiment with Populus tremuloides (Zak et al, 2000a). In this soil, fine root biomass was 1\100 of the labile pool of organic matter and 1\1000 of the total organic matter content.…”
Section: Soil Microbial Biomassmentioning
confidence: 77%
“…Reports of microbial immobilization are more abundant in the literature (Table 5), but only a handful of investigators have measured gross N mineralization and microbial immobilization in concert (Berntson & Bazazz, 1997, 1998Hungate et al, 1997a,c ;Mikan et al, 2000 ;Zak et al, 2000a). Beneath grasses and intact grasslands, microbial immobilization exhibited large declines (-64%) and large increases (j501%) ; with few exceptions, these responses are not statistically significant (Table 5).…”
Section: Soil Nitrogen Dynamicsmentioning
confidence: 98%
See 3 more Smart Citations